THE SALE OF SNACKS AND BEVERAGES IN PUBLIC SCHOOLS: ANALYSIS OF A STATE REGULATORY - José Divino Lopes Filho; Larissa Loures Mendes (Universidade do Estado do Rio de Janeiro, 2016)
Encouraging an adequate and healthy food in schools is a common practice in many countries and has been increasingly regulated in the municipalities and states. However, the laws created do not seem to guarantee that the quality of all the food available in these institutions is appropriate. In the state of Minas Gerais, the Law No. 18,372 of 2009 regulates the sale of snacks and beverages of low nutritional value in state schools. The objective was to verify compliance with regulatory trade for snacks and drinks in public schools in the city of Belo Horizonte. A total of 156 schools which correspond to 87% of the total were evaluated. For data collection, a standardized questionnaire developed by the Coordinator of the School Feeding Program of Minas Gerais was used. The data of the infrastructure of schools and the food sold inside there were collected. A database was developed from which it could investigate the compliance with the law, comparing what was marketed with the restrictions established by law. It was verified that 78 schools (50.6%) were selling foods with the excess of Trans fat, saturated fat, sodium, sugars and calories. The frequencies found of the selling of food prohibited by law were: salty baked goods, 82.4%; artificial beverages, soft drinks and artificial juices, 54.8%; embedded derivate, 42.7%; bacon, straw potato, ice cream and greasy sauces, 34.2%. The regulation of the food sales in schools can be considered an important step in promoting healthy eating at school, but the constant supervision is necessary for compliance with legislation. DOI: 10.12957/demetra.2016.19641